Chronic immune activation in the T cell compartment of HCV/HIV-1 co-infected patients - Sandberg, Johan K.; Falconer, Karolin; Gonzalez, Veronica D. (Virulence, 2010)
Activation of innate and adaptive immune mechanisms in response to infection is necessary to control and clear infections. However, chronic immune activation in human immunodeficiency virus 1 (HIV-1) infection has a series of detrimental effects and is a major driving force in HIV-1 disease progression. We recently found that patients with chronic hepatitis C virus (HCV)/HIV-1 co-infection display sharply elevated immune activation as determined by expression of CD38 in T cells. High immune activation was observed despite that these patients were on effective antiretroviral therapy (ART), which usually brings down activation levels in HIV-infected people. HCV treatment with pegylated interferon-α (IFNα) and ribavirin reduced activation, and this was at first glance unexpected as IFNα is believed to be involved in driving activation. Here, we briefly summarize these findings and discuss them in context of the emerging roles of the gut barrier and the liver in chronic immune activation and viral disease progression.